Circuitos de la economía urbana y gourmetización turística en mercados de chile y méxico - Costa, Everaldo Batista da (2024)
Traditional markets must be seen as complex social units, which connect both internal dynamics between tenants and costumers, and external ones, which redefine the two circuits of urban economy and a national-international productive spatial circuit. Thus, the aim of the research is to analyze the two circuits of urban economy in association with touristic gourmetization in two traditional markets: Central de Santiago (Chile) and San Juan Pugibet (Mexico). Methodologically, the process took place as follows: (i) literature review on: (a) the two circuits of urban economy in Latin America and (b) commercial-tou ristic gourmetization in traditional Latin American markets; (ii) empirical identification of the dialectic of the two circuits of urban economy linked to touristic gourmetization and its impact on the analyzed markets. A mixed methodological order design was adopted, encompassing (a) direct observation, (b) semi-structured interviews, (c) data collection to develop a cartography of the local-national-international productive spatial circuit ac tivated by both establishments, as well as synthesis charts of the two circuits of urban economy related to them.